2017
DOI: 10.1155/2017/4867060
|View full text |Cite
|
Sign up to set email alerts
|

Age-Adjusted D-Dimer in the Prediction of Pulmonary Embolism: Does a Normal Age-Adjusted D-Dimer Rule Out PE?

Abstract: Risk assessment for pulmonary embolism (PE) currently relies on physician judgment, clinical decision rules (CDR), and D-dimer testing. There is still controversy regarding the role of D-dimer testing in low or intermediate risk patients. The objective of the study was to define the role of clinical decision rules and D-dimer testing in patients suspected of having a PE. Records of 894 patients referred for computed tomography pulmonary angiography (CTPA) at a University medical center were analyzed. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…[34][35][36] This is thought to increase the specificity of the D-dimer in the elderly. [37][38][39] Clinical studies indicate that the D-dimer values are slightly higher in women, which is in accordance with the results of this study. As was the case with the results of other researchers, the difference was not significant in the present study either.…”
Section: Discussionsupporting
confidence: 92%
“…[34][35][36] This is thought to increase the specificity of the D-dimer in the elderly. [37][38][39] Clinical studies indicate that the D-dimer values are slightly higher in women, which is in accordance with the results of this study. As was the case with the results of other researchers, the difference was not significant in the present study either.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that there is limited reliability of the D-dimer value as a diagnostic cut-off in hospitalized patients [18][19][20] . Some studies also suggest age-adjusted value of D-dimers would work better as a diagnostic cutoff for both hospitalized patients and outpatients [23][24][25] . Current guidelines, however, and the sGS do not make general use of age-adjusted D-dimer values.…”
Section: Discussionmentioning
confidence: 99%
“…El ELISA (enzyme linked immunosorbent assay) cuantitativo u otros análisis derivados de este tienen una sensibilidad diagnóstica del 95% o superior, por lo que pueden utilizarse para excluir la EP en pacientes con una probabilidad previa a la prueba baja o moderada 4,9,23,[35][36][37] . La especificidad del dímero D disminuye con la edad, hasta casi un 10% en pacientes mayores de 80 años 4,36 ; el uso de puntos de corte ajustados por edad mejora el rendimiento del estudio del dímero D en ancianos 4,36 .…”
Section: Enzyme Linked Immunosorbent Assayunclassified
“…La especificidad del dímero D disminuye con la edad, hasta casi un 10% en pacientes mayores de 80 años 4,36 ; el uso de puntos de corte ajustados por edad mejora el rendimiento del estudio del dímero D en ancianos 4,36 . Valores de corte ajustados por edad (edad × 10 μg/l por encima de los 50 años) permitieron aumentar la especificidad del 34 al 46% conservando una sensibilidad superior al 97% 4,23,36,37 .…”
Section: Enzyme Linked Immunosorbent Assayunclassified